Gene Structure and Expression Analysis of Insulin-Like Peptide in the Pacific White Shrimp Litopenaeus vannamei - Manwen SU; Xiaojun ZHANG; Jianbo YUAN; Xiaoxi ZHANG; Ming YANG; Fuhua LI (Progress in Fishery Sciences, 2024)
Insulin-like peptide (ILP) is a member of the insulin superfamily with evolutionary conservation and is one of the most important factors affecting animal life activities. In this study, a full-length of ILP1 gene in Pacific white shrimp, Litopenaeus vannamei, was cloned, and the mRNA length consisted of 812 bp with an open reading frame (ORF) of 543 bp, encoding 180 amino acids. Sequence analysis showed that the predicted molecular weight of LvILP1 protein was 20.81 kDa, and the theoretical isoelectric point was 9.45 and the instability coefficient was 96.20. There was a signal peptide, no transmembrane structure. It was deduced that it was located outside the cell and is an alkaline unstable secreted protein. Structure prediction found that LvILP1 protein had the conserved IlGF domain of the insulin superfamily, which was composed of the N-terminal signal peptide, B-chain, C-peptide and A-chain, as well as six conserved cysteine sites and two cleavage sites. Phylogenetic analysis found that LvILP1 was most closely related to ILP7 in Penaeus monodon, and clustered with ILP1 of Crustaceans to form a branch, and then clustered with ILP7 of Invertebrate, Relaxin, Insulin and Insulin-like growth factor (IGF) of vertebrate; ILP7 of Invertebrate was evolutionarily closest to outgroup sea anemone ILP1, suggesting that it may be more similar to the ancestor gene of the insulin superfamily. Transcription factor prediction found that the possible transcription factors of LvILP1 are Forkhead box protein O3 (FoxO3), Glucocorticoid receptor (GR), CAAT region/enhancer binding protein (C/EBP) and Signal transduction and transcription activator protein (STAT); The protein interaction analysis found that LvILP1 interacted with Insulin receptor (IR) on the cell membrane, nerve signaling molecules (VGLUT1, SYT 1_3), Glycoprotein hormone beta 5 (GPHB5), Bursicon alpha, etc. By analyzing the biological function analysis of these transcription factors and interacting proteins, it is speculated that LvILP1 may play an important role in regulating shrimp growth and development, response to hormonal stimulation, nervous system homeostasis, carbohydrate homeostasis, postmolt tissue remodeling and reproductive development. The analysis showed that LvILP1 was expressed in the early developmental stage of shrimp, and expressed in all tissues of adults, but the expression level in the eye stalk was the highest. This study provides important information for in-depth understanding of the structure, evolution, function and expression of ILP in shrimp, as well as clues for molecular breeding and healthy farming of shrimp.